2009
DOI: 10.1139/b09-060
|View full text |Cite
|
Sign up to set email alerts
|

Low soil temperature reduces the positive effects of high nutrient supply on the growth and biomass of white birch seedlings in ambient and elevated carbon dioxide concentrations

Abstract: To investigate the interactive effects of soil temperature (Tsoil) and nutrient supply on the responses of growth and biomass of white birch ( Betula papyrifera Marsh.) to atmospheric carbon dioxide concentration ([CO2]), seedlings were grown under two [CO2] (360 and 720 µmol·mol–1), three Tsoil (5, 15, and 25 °C initially, increased to 7, 17, and 27 °C one month later), and three nutrient regimes (Low: N–P–K = 4:1.8:3.3 mg·L–1; Intermediate: N–P–K = 80:35:66 mg·L–1; and High: N–P–K = 160:70:132 mg·L–1) for 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 58 publications
2
6
0
Order By: Relevance
“…In the present study, positive responses to elevated [CO 2 ] were observed for all examined morphological ( H and RCD) and biomass (shoot, root, and total biomass) growth parameters. Similar observations have been reported previously for white birch (Zhang et al 2006, Cao et al 2008, Ambebe et al 2009, Ambebe and Dang 2010) and other boreal broad‐leaf and conifer tree species including trembling aspen ( Populus tremulodes Michx. ; Liu et al 2006), Sitka spruce ( Picea sitchensis (Bong.)…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the present study, positive responses to elevated [CO 2 ] were observed for all examined morphological ( H and RCD) and biomass (shoot, root, and total biomass) growth parameters. Similar observations have been reported previously for white birch (Zhang et al 2006, Cao et al 2008, Ambebe et al 2009, Ambebe and Dang 2010) and other boreal broad‐leaf and conifer tree species including trembling aspen ( Populus tremulodes Michx. ; Liu et al 2006), Sitka spruce ( Picea sitchensis (Bong.)…”
Section: Discussionsupporting
confidence: 89%
“…With cold T soil sites underlain by permafrost, warm south‐facing slopes and newly burnt sites, and several transitional areas between the cold and warm extremes, the boreal forest is one of the most variable terrestrial ecosystems in terms of T soil . The growth of boreal trees show marked T soil dependency (Landhäusser and Lieffers 1998, King et al 1999, Peng and Dang 2003, Aphalo et al 2006, Zhang and Dang 2007, Ambebe et al 2009, Ambebe and Dang 2010). Adverse effects of cold T soil on growth result from impairments of root growth/physiological uptake capacity, nutrient translocation, and CO 2 assimilation among others (Kaufmann 1977, DeLucia et al 1992, Kaspar and Bland 1992, Waring and Running 1998, Grossnickle 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Reductions in g s and shoot water potential in turn can affect photosynthetic responses to CO 2 elevation [5,25]. For example, low T soil is found to reduce the positive effect of CO 2 elevations on photosynthesis in various tree species [5,[26][27][28][29]. Low T soil can also reduce the synergistic effect of CO 2 elevation and high N supply on photosynthesis [28] and growth [29].…”
Section: Introductionmentioning
confidence: 99%
“…For example, low T soil is found to reduce the positive effect of CO 2 elevations on photosynthesis in various tree species [5,[26][27][28][29]. Low T soil can also reduce the synergistic effect of CO 2 elevation and high N supply on photosynthesis [28] and growth [29]. However, the decline in g s at low T soil does not necessarily lead to a reduction in photosynthesis in all species [30,31].…”
Section: Introductionmentioning
confidence: 99%